การเปรียบเทียบความเที่ยงของแบบสอบอัตนัยประยุกต์สำหรับวัดความสามารถในการใช้วิธีการทางวิทยาศาสตร์ในวิชาฟิสิกส์ ภายใต้จำนวนเหตุการณ์และจำนวนผู้ตรวจที่ต่างกัน: การประยุกต์ใช้ทฤษฎี การสรุปอ้างอิงความน่าเชื่อถือของผลการวัด - ผดุงผล สุภชิต; ตังธนกานนท์ กมลวรรณ (An Online Journal of Education, 2018)
The purpose of this research were 1) to develop modified essay question test for measuring the abilities in using scientific method in physic 2) to compare the reliability of the modified essay question test for measuring the abilities in using scientific method in physic under defferent numbers of event and rater by application of Generalizability Theory. Sample were 94 mattayomsuksa 4 students. Research instruments were modified essay question test for measuring the abilities in using scientific method in physic. Pearson’s Product Moment Correlation and G – Coefficient were used to analyze the data. It was found that 1) The developed modified essay question test for measuring the abilities in using scientific method in physic are 4 events, each with 5 questions, total 20 questions. Each question is in line with the abilities in using scientific method by the researcher to synthesize the ideas and research involved in measuring and assessing abilities. In the use of scientific methods, Question 1 of all events will measure the ability to identify problems. Question 2 of all events will measure the ability to hypothesize. Question 3 of all events will measure the ability to test hypotheses. Question 4 of every event will measure the ability to gather information. And question 5 of all events will measure the ability to draw conclusions. The test validity obtained from the test results was 0.789, 2) Result of the comparisons of reliability of modified essay question test for measuring the abilities in using scientific method in physic under difference numbers of event and rater revealed that under all of the conditions person variance was highest and higher reliability when the number of events increases and the number of raters increases.